The public interest standard and deregulation the impact of the Fairness Doctrine. - Goldoff, Anna C. (1996)
"For thirty-eight years, the Fairness Doctrine was the "linchpin" or core of the public interest standard of the 1934 Communications Act, regulating commercial broadcasting in the United States. In 1987, the Federal Communications Commission (FCC) repealed the doctrine. The paper here relates a policy analysis of the Fairness Doctrine which was incorporated into the proposed FAIRNESS IN BROADCASTING ACT OF 1989, codifying the doctrine. Key personnel in the broadcasting industry were interviewed to find out their understanding of and attitudes towards "fairness", compliance, and the overall impact of Fairness Doctrine policies on the clientele. The political and administrative struggle over the Fairness Doctrine continues, amid the current administration's drive to reregulate the cable and commercial broadcasting industries. The passage of the Cable Television Consumer Protection Act of 1992 and recent efforts in the 103rd Congress to revive the Fairness Doctrine, indicate that the era of pure deregulation is over"
Keywords: Fairness doctrine (Broadcasting) - United States; Communication; Mass media